2017
DOI: 10.1021/acs.orglett.7b02621
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinoyl Radical Initiated Vicinal Cyanophosphinoylation of Alkenes

Abstract: A double-functionalization reaction of alkenes through Mn(OAc)-mediated phosphinoyl radical addition followed by CuCN-catalyzed cyanation is introduced. This one-pot reaction is performed under mild conditions to afford vicinal cyanophosphinoylation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Regarding the mechanism, we hypothesized that b-hydroxyl nitrile would be a plausible intermediate involved in this transformation, given the fact that the use of water as co-solvent under oxidative conditions. In the presence of copper and Selectfluor, styrene was oxidized to vinyl radical cation B, which could be trapped by water to form benzyl radical C. Similar to the previously reported Cu-catalyzed radical cyanations [35][36][37][38]47,48], the reaction of LnCu II (CN) A (generated in situ) with alkyl radical F followed by reductive elimination would furnish b-hydroxyl nitrile F. Elimination of H 2 O would afford the vinyl nitrile product. We subjected pre-prepared 44 into the reaction conditions, while no desired vinyl nitrile was observed in 15 min, precluding the possibility of this pathway (Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Regarding the mechanism, we hypothesized that b-hydroxyl nitrile would be a plausible intermediate involved in this transformation, given the fact that the use of water as co-solvent under oxidative conditions. In the presence of copper and Selectfluor, styrene was oxidized to vinyl radical cation B, which could be trapped by water to form benzyl radical C. Similar to the previously reported Cu-catalyzed radical cyanations [35][36][37][38]47,48], the reaction of LnCu II (CN) A (generated in situ) with alkyl radical F followed by reductive elimination would furnish b-hydroxyl nitrile F. Elimination of H 2 O would afford the vinyl nitrile product. We subjected pre-prepared 44 into the reaction conditions, while no desired vinyl nitrile was observed in 15 min, precluding the possibility of this pathway (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Given the importance of vinyl nitriles, we became interested in developing a catalytic cyanation protocol to access alkenyl nitriles from readily available alkenes [35][36][37][38][39][40], with particular attention on site-selectivity of vinyl CÀH bonds. Inspired by the elegant work on branch-selective oxidative couplings of olefins [41][42][43][44], we recognized that a similar, branch-selective, catalytic oxidative cyanation of olefins might provide an effective strategy for the synthesis of a-cyano alkenes normally difficult to access.…”
Section: Introductionmentioning
confidence: 99%
“…TMSCN (2 eq) was also applied in a double functionalization of styrenes through manganese‐mediated phosphinoyl radical addition followed by a copper‐catalyzed cyanation under mild conditions. The addition products 60 (examples 61‐63 ) were isolated in yields from 32% to 90% (scheme ) . This method might be of interest for chemists working in the phosphorus field searching for a shortcut.…”
Section: Cyano‐group Sourcesmentioning
confidence: 99%
“…The addition products 60 (examples 61-63) were isolated in yields from 32% to 90% (scheme 13). 43 This method might be of interest for chemists working in the phosphorus field searching for a shortcut.…”
Section: Trimethylsilylcyanide (Tmscn)mentioning
confidence: 99%
“…The addition of these radicals to unsaturated systems is used to generate new C-C bonds [26][27][28]. Manganese (III) acetate [29][30][31][32][33] and cerium(IV) ammonium nitrate (CAN) [34][35][36][37][38] are widely used in these reactions. Our research group has reported radical addition and cyclization reactions with CAN [39][40][41][42] and radical cyclization reactions of 1,3-dicarbonyl derivatives with various unsaturated systems, such as conjugated amide derivatives [43][44][45][46][47]and heteroaromatic conjugated alkenes [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%